Pengaruh Konseling Kelompok Terhadap Perilaku Agresif Siswa di SMKN 4 Mataram - I Made Gunawan; Aluh Hartati; Fatimah Sahil Mulachela (Jurnal Paedagogy, 2020)
The purpose of this study was to examine the application of group counseling in reducing students' aggressive behavior. The research method used is the experimental method. The population in this study amounted to 76 students and the sample used to obtain data was 8 students who had a high score of aggressive behavior (purposive sampling). The data collection techniques used were questionnaires, observation, interviews and documentation. While the data analysis technique of this research uses the t-test formula. The results of this study indicate that the data analysis t count is 5.401 with a t table value at the 5% significance level with db (N-1) = 7 of 2.365. Thus the t value is greater than the t value in the table (5.401> 2.365), so it can be concluded that there is an effect of group counseling on aggressive behavior of class XI students in hospitality accommodation at SMKN 4 Mataram.